"Why can't you sit still?"The effect of daily physical activity on childhood inattention/hyperactivity and the educational gender gap. (September 2021) - Chen, Kelly; Phipps, Shelley
Abstract: Despite the compelling evidence of the long-run consequences of childhood inattention/hyperactivity and harmful side effects of stimulant medication, relatively little is known about accessible non-pharmacological options to reduce inattentive/hyperactive behaviours. This study evaluates the effect of daily exercise on inattentive/hyperactive behaviours among young children by leveraging evidence from a quasi-experiment generated when 3 Canadian provinces adopted mandatory requirements for all students in grades 1 through 6 to participate in 20–30 min of daily physical activity at school between 1994 and 2009. By exploiting plausibly exogenous variations in the timing of implementation and duration of physical activity mandated as well as over 20, 000 observations on a sample of nationally representative children, our difference-in-differences estimates indicate that brief bouts of daily exercise at school effectively reduce inattention/hyperactivity in children – with the beneficial effect enhanced by the duration of exercise mandated. Importantly, most of the exercise effect is concentrated on boys. Since boys' higher rates of inattention/hyperactivity contribute to the explanation for boys' lagging academic motivation and achievement, we argue that providing more scope for physical activity during the school day might be a feasible policy option not only for reducing inattentive/hyperactive behaviours, but also for helping to close the educational gender gap in the longer run. Highlights: Daily exercise is a non-pharmacological option to reduce inattention/hyperactivity. Brief bouts of daily exercise reduce inattention/hyperactivity in young children. Most of the exercise effect is concentrated on boys. Mandate of daily exercise can help improve boys' relative motivation/performance.